Produção de fertilizantes sustentáveis de liberação lenta de ureia: utilização de biopolímeros, argila e serragem como matérias- primas - Maia, Hermógenes Bezerra (2023)
Eucalyptus is a highly cultivated plant worldwide. In Brazil, its cultivation directly contributes to the expansion of the Brazilian tree industry. However, eucalyptus processing generates large volumes of waste, mainly in the form of sawdust, which has a high content of cellulose, lignin, and hemicellulose that can be incorporated into the production of slow-release fertilizers (SRFs), aiding in moisture absorption, nutrient adsorption, and encapsulation, thereby enhancing the regulatory efficiency of SRFs' release. Therefore, in this study, different formulations of slow-release fertilizers were synthesized using eucalyptus sawdust, alginate, chitosan, clay, and urea. Fourier-transform infrared (FTIR) spectra showed characteristic bands related to the axial deformation of O–H and N–H amine groups, presented by alginate, clay, sawdust, and urea; bands characteristic of the axial deformation of the C=O bond, as observed in the spectra of sawdust and urea; and the band corresponding to the deformation of the C–H bond of lignin and carbohydrates in sawdust. The fertilizer spheres were characterized by elemental analysis (CHN), revealing carbon contents of 14.4-24.8%, hydrogen contents of 6.27-8.61%, and nitrogen contents of 9.34-26.0%. A calibration curve for urea in water was constructed using UV-Vis spectrophotometry, yielding a coefficient of determination (R2) of 0.9986, demonstrating the method's efficiency in determining urea. Water release tests revealed that the fertilizers release urea slowly, reaching maximum release after 540 minutes. Kinetic models were applied to the water release assay results, and it was determined that the release of fertilizers follows a pseudo-Fickian behavior. FERT 1, FERT 2, and FERT 4 exhibited release rates of 15.00%, 13.00%, and 10.30% of nitrogen (N) in the soil within the first 24 hours, 75.00%, 60.00%, and 64.70% in 28 days, respectively, and 100% release after 35 days for all fertilizers. The soil release study revealed that FERT 1, FERT 2, and FERT 4 can be classified as slow-release fertilizers according to Trenkel. Among the four v fertilizers produced, FERT 2 exhibited the most gradual nutrient release in the soil. The degradation rates in the soil were 82.0%, 46.6%, 70.0%, and 77.0% for FERT 1, FERT 2, FERT 3, and FERT 4, respectively. Finally, the results demonstrated the potential use of sawdust in combination with alginate, chitosan, and clay for the formation of slowrelease fertilizers, providing a viable and promising application for eucalyptus waste.